Interplay between pinning energy and vortex interaction in YBa2Cu3O7-delta with oriented twin boundaries in tilted magnetic fields: Bitter decoration and tilt-modulus measurements - Herbsommer, J.A.; Nieva, G.; Luzuriaga, J.; Nieva, Gladys (American Physical Society, 2000)
Fil: Herbsommer, J.A. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina